Impact of macroscopic on-site evaluation (MOSE) on accuracy of endoscopic ultrasound-guided fine-needle aspiration/biopsy of solid lesions - Hussein Okasha; Ahmed Ebrahim; Ihab Samih; Mohammed Sayed (Society of Gastrointestinal Intervention, 2024)
Background : : Endoscopic ultrasound (EUS) tissue acquisition requires rapid on-site evaluation to improve diagnostic yield with less needle passes; however, this is not readily available in all centers, also it increases the duration and the cost of the procedure. Macroscopic on-site evaluation (MOSE) is the direct assessment of the tissue sample provided by EUS-guided fine needle biopsy (EUS-FNB) macroscopically, to detect whether it is sufficient or not. Aim of this study was to define the role of MOSE in judging the adequacy of the tissue core specimens and to evaluate its diagnostic yield and accuracy.Methods : : This prospective study was conducted at our institution with 215 participants of both genders presenting for evaluation of solid or mixed solid and cystic lesions by MOSE technique by EUS-fine needle aspiration (FNA) or FNB.Results : : In obtaining conclusive sample MOSE score 1 sensitivity was 68.2%, specificity was 75%, positive predictive value (PPV) was 99.3, negative predictive value (NPV) was 4.3 and overall accuracy was 68.4, in MOSE score 2 sensitivity was 88%, specificity was 75%, PPV was 99.5, NPV was 10 and overall accuracy was 87, in MOSE 2 (FNB) sensitivity was 92%, Specificity was 67%, PPV was 99.4, NPV was 12, 5 and overall accuracy was 92. There was no statistically significant difference between the two groups with conclusive and inconclusive cytopathological results regarding size of the needle, number of needle passes, type of the needle and the specimen acquisition method.Conclusion : : Using MOSE for assessment of adequacy of the sample obtained by EUS-FNB showed higher diagnostic yield compared to conventional method using different needle sizes.